The Decisive Network: Producing Henri Cartier-Bresson at Mid-Century. Issue 2 (2nd April 2016) - Bair, Nadya
Abstract : Henri Cartier-Bresson's photobook The Decisive Moment (1952) popularised the notion that the best photographs are made by the patient and gifted photographer who captures a fleeting moment with just one click of the shutter, creating an image with internal geometry and balance. The book solidified Cartier-Bresson's reputation as an artist working with a camera and it encouraged scholars, curators, and hobbyists to understand photography as the product of trained individual vision and talent. Yet the book's emphasis on personal vision also deflected attention away from the collective efforts and infrastructure necessary to promote Cartier-Bresson's practice as art. By shifting our attention to the decisive network of magazine editors, book publishers, printers, and curators who helped Cartier-Bresson onto a highly orchestrated road to fame at mid-century, this article considers the ways in which collective work is central to the material and social history of photography, and how these realities challenge the decisive moment's paradigm of individual and inspired creation.